Cardiovascular autonomic profile in women with constitutional hypotension. Issue 10 (October 2018) - Jacob, Giris; Barbic, Franca; Glago, Meytal; Dipaola, Franca; Porta, Alberto; Furlan, Raffaello
Abstract : Background: Constitutional hypotension (CHT) is defined as a SBP below 105 mmHg. As autonomic-related symptoms are frequently reported in CHT, these symptoms suggest that the cardiovascular autonomic control is perturbed in individuals with CHT. Methods: We investigated the autonomic cardiovascular control of 15 women with CHT and 12 women with NBP (SBP >110 mmHg). We monitored BP and ECG for autonomic function test. Supine and head up tilt (HUT) spectral analysis of RR interval and BP variability, baroreflex sensitivity and plasma levels of plasma renin activity and aldosterone were determined. M-mode echocardiogram was used to determine the left ventricle mass. Results: SBP and DBP were lower in CHT (97 ± 1.5 and 54 ± 1.5 mmHg) than in NBP (126 ± 3 and 70 ± 4 mmHg, P < 0.001 for both), whereas heart rate was comparable (65 ± 1.5 and 63 ± 3 bpm). CHT compared with NBP had lower Valsalva's ratio and BP phase IV overshooting, 1.7 ± 0.07 vs. 2 ± 0.07 ( P < 0.05) and 19 ± 2.4, and 28 ± 3 mmHg ( P < 0.05), respectively. BRSseq, alpha LF and LFRR /HFRR were greater in CHT (29.2 ± 0.7 and 39.1 ± 4.7 ms/mmHg and 1.4 ± 0.2) compared with NBP (25 ± 1.6 and 20.1 ± 2.5 ms/mmHg and 0.7 ± 01, [ P < 05, for all]). LFSAP was lower in CHT (0.8 ± 0.2) than in NBP (1.5 ± 0.3 mmHg 2, P < 0.02). HUT data were similar. Supine and HUT aldosterone and PRA were higher in CHT. Left ventricle mass was lower in CHT. Conclusion: We conclude that the cardiovascular autonomic control in women with CHT is characterized by a low sympathetic vascular tone and increased baroreceptor sensitivity. Also, it seems that these women have a compensated primary hypovolemia, which warrants further investigation.